2019
DOI: 10.3389/fpsyg.2019.02647
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Older Volunteering on Wellbeing: An International Comparison

Abstract: Healthier aging implies lower health service expenditure and the possibility for individuals to make a longer and more valuable contribution to society. Lifestyles, including volunteering, affect our health. The policy implications of the present study are that it aims to broaden the state of knowledge and be useful to public decision-makers: if voluntary activities enhance the integration of older people into society, their participation will help to generate economic resources and improve their own welfare; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 82 publications
(79 reference statements)
2
25
0
1
Order By: Relevance
“…An impact of occupational factors even when adjusted for factors at other levels is a particularly interesting finding for understanding suicide in the working‐age population. Studies usually focused on one or two particular levels (e.g., socioeconomic (Alicandro et al, 2019; Basta et al, 2018; Borrell et al, 2020; Bossard et al, 2016; Chan et al, 2014; Hagedoorn et al, 2020; Harper et al, 2015; Hiyoshi et al, 2018; Milner, Niven, et al, 2015; Vanderoost et al, 2013), social‐behavioral (Deckert et al, 2015; Gearing & Alonzo, 2018; Gil‐Lacruz et al, 2019; Stack & Laubepin, 2019; Torgler & Schaltegger, 2014; Tsai et al, 2014) or occupational level (Alexopoulos et al, 2016; Bossard et al, 2016; Cohidon et al, 2010; Encrenaz et al, 2016; Guseva Canu et al, 2019; Hawton et al, 2011; Klingelschmidt et al, 2020; McIntosh et al, 2016; Milner et al, 2014; Milner, Smith, et al, 2015; Milner et al, 2013; Mustard et al, 2010; Ringgenberg et al, 2018; Roberts et al, 2013; Stark et al, 2006; Tanaka et al, 2017; Wada et al, 2016)) and might have over‐ or underestimated their respective contributions.…”
Section: Discussionmentioning
confidence: 99%
“…An impact of occupational factors even when adjusted for factors at other levels is a particularly interesting finding for understanding suicide in the working‐age population. Studies usually focused on one or two particular levels (e.g., socioeconomic (Alicandro et al, 2019; Basta et al, 2018; Borrell et al, 2020; Bossard et al, 2016; Chan et al, 2014; Hagedoorn et al, 2020; Harper et al, 2015; Hiyoshi et al, 2018; Milner, Niven, et al, 2015; Vanderoost et al, 2013), social‐behavioral (Deckert et al, 2015; Gearing & Alonzo, 2018; Gil‐Lacruz et al, 2019; Stack & Laubepin, 2019; Torgler & Schaltegger, 2014; Tsai et al, 2014) or occupational level (Alexopoulos et al, 2016; Bossard et al, 2016; Cohidon et al, 2010; Encrenaz et al, 2016; Guseva Canu et al, 2019; Hawton et al, 2011; Klingelschmidt et al, 2020; McIntosh et al, 2016; Milner et al, 2014; Milner, Smith, et al, 2015; Milner et al, 2013; Mustard et al, 2010; Ringgenberg et al, 2018; Roberts et al, 2013; Stark et al, 2006; Tanaka et al, 2017; Wada et al, 2016)) and might have over‐ or underestimated their respective contributions.…”
Section: Discussionmentioning
confidence: 99%
“…Third, there are important differences among welfare systems in issues related to gender differences and volunteering activities. For example, for senior women in southern Europe, if they engage in volunteering activities, they engage in religious organizations that do not carry out voluntary activities, and, in most cases, they are linked to religious organizations [4].…”
Section: Discussionmentioning
confidence: 99%
“…The quality of aging depends on multiple factors, including access to and use of educational and health services, biological processes, environmental factors, and specific individual behaviors and socioeconomic characteristics [3][4][5]. As such, it is essential to promote health throughout the entire lifespan of individuals in order to ensure their well-being in old age [6].…”
Section: Introductionmentioning
confidence: 99%
“…Volunteering in elderly people has positive effects (Gil-Lacruz et al, 2018 ; Krause & Rainville, 2018 ). Among its benefits, research has revealed that senior volunteers are more protected from health risks related to retirement and physical inactivity than those who do not volunteer (Gil-Lacruz et al, 2019 ; Wilson & Musick, 2012 ). According to data of Volunteurope report ( 2012 ), the percentage of elderly people in volunteering varies substantially among the European countries, with high rates in the Netherlands (20%), and low rates in Greece (3%).…”
Section: Introductionmentioning
confidence: 99%